2020
DOI: 10.3389/fphar.2020.01136
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine Inhibits Renal Tubular Epithelial Cells to Mesenchymal Transition in Diabetic Rats via Upregulation of Sirt1

Abstract: Trimetazidine (TMZ), as a metabolic regulator, is effective in treatment of coronary atherosclerotic heart disease with rare side effects in the clinic for long years. Interestingly, studies have shown that TMZ protects against several acute kidney injuries (AKI). However, the effect of TMZ on chronic kidney diseases (CKD) remains unknown. This study aimed to investigate the role of TMZ in diabetic nephropathy (DN) and its potential mechanisms. A rat model of DN was established in male Sprague-Dawley rats by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…In DKD, EMT of renal tubular epithelial cells is believed to participate in the progress of tubulointerstitial fibrosis through the accumulation of renal matrix protein. EMT induced by hyperglycemia is generally considered to be the initial factor leading to matrix accumulation and deposition, so EMT is also considered to be an important mechanism of renal fibrosis and renal dysfunction in DKD [ 27 ]. Therefore, targeting EMT is considered a potential therapy to delay the progression of tubulointerstitial fibrosis in DKD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In DKD, EMT of renal tubular epithelial cells is believed to participate in the progress of tubulointerstitial fibrosis through the accumulation of renal matrix protein. EMT induced by hyperglycemia is generally considered to be the initial factor leading to matrix accumulation and deposition, so EMT is also considered to be an important mechanism of renal fibrosis and renal dysfunction in DKD [ 27 ]. Therefore, targeting EMT is considered a potential therapy to delay the progression of tubulointerstitial fibrosis in DKD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TGF-β 1 mRNA and the TGF-β 1 protein in the kidney tissue of people with diabetes is increased ( Zhang et al, 2017 ). TGF-β 1 is directly involved in the epithelial-to-mesenchymal transition process of DKD, leading to renal interstitial fibrosis ( Zheng et al, 2016 ; Yang Y. et al, 2020 ), and it can activate the downstream Smad signaling pathway, thereby mediating fibrogenesis ( Hathaway et al, 2015 ). The role of TMAO in promoting fibrosis has also been demonstrated in many studies.…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is a nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylase that exerts anti-inflammatory and anti-oxidative effects on pathological process in several organs, including kidney 25 , 26 . In the present research, we found that TF inhibited CaOx-induced kidney oxidative stress injury and alleviated kidney crystal deposition by regulating miR-128/SIRT1 axis.…”
Section: Introductionmentioning
confidence: 99%